Domiciliary occupational therapy for patients with stroke discharged from hospital: randomised controlled trial. Issue 7235 (4th March 2000) - Gilbertson, Louise; Langhorne, Peter; Walker, Andrew; Allen, Ann; Murray, Gordon D
Abstract: Objective: To establish if a brief programme of domiciliary occupational therapy could improve the recovery of patients with stroke discharged from hospital. Design: Single blind randomised controlled trial. Setting: Two hospital sites within a UK teaching hospital. Subjects: 138 patients with stroke with a definite plan for discharge home from hospital. Intervention: Six week domiciliary occupational therapy or routine follow up. Main outcome measures: Nottingham extended activities of daily living score and "global outcome" (deterioration according to the Barthel activities of daily living index, or death). Results: By eight weeks the mean Nottingham extended activities of daily living score in the intervention group was 4.8 points (95% confidence interval −0.5 to 10.0, P=0.08) greater than that of the control group. Overall, 16 (24%) intervention patients had a poor global outcome compared with 30 (42%) control patients (odds ratio 0.43, 0.21 to 0.89, P=0.02). These patterns persisted at six months but were not statistically significant. Patients in the intervention group were more likely to report satisfaction with a range of aspects of services. Conclusion: The functional outcome and satisfaction of patients with stroke can be improved by a brief occupational therapy programme carried out in the patient's home immediately after discharge. Major benefits may not, however, be sustained.